Interdisciplinary approaches, interpretations and key research relationships - Board, Editorial (Leadership, Society, Strategic Visions, 2021)
Theoretical and applied dimensions, approaches for analysis and interpretation. Methodology of understanding – facts, context, endogenous and exogenous factors, interdisciplinary knowledge sharing, consensus matrix and toolkit; new civilization philosophy, way of thinking, integrative criteria; the man of present and future – parameters for constant investments, transformations and balances, index combinations, comparisons and preconditions.